"Seriously, Australia, why are you so stingy with Wi-Fi?": customer satisfaction with Wi-Fi speed in Australian hotels and lessons for public Wi-Fi provision. (2nd September 2021) - Grechyn, Viktor; McShane, Ian
Abstract : Purpose: This paper aims to analyse whether the speed of Wi-Fi in hotels influences customer satisfaction with hotels and the implications of this for the provision of Wi-Fi by commercial and governmental bodies seeking to boost tourism. Design/methodology/approach: Regression analysis on data from Australian hotels (191 entries) and 111 responses to a national survey of local government authorities on public Wi-Fi (PWF) provision were combined with a literature review and content analysis of online reviews by hotel customers. Findings: If Wi-Fi quality rises by 1%, customer satisfaction with the hotel increases by 0.376/100 units. In the areas where hotel Wi-Fi is of better quality, PWF provided by the local government is also of better quality; the reverse statement is also true. Practical implications: Tourists value continuous access to Wi-Fi, whether provided by commercial or public bodies. It is imperative for hotels and local governments seeking to boost tourist activity to invest in quality Wi-Fi networks. However, to assist this, national policies should address spatial disparities in broadband infrastructure revealed in the study. Originality/value: This study looks beyond a conventional distinction between the private and public provision of Wi-Fi to examine the shared interests of industry and government in this essential component of tourist infrastructure. The study is unique in the English-speaking literature for its focus on the link between the quality of Wi-Fi provision and customer satisfaction, with original results and discussion providing a rationale for investing in quality Wi-Fi networks. Abstract : 认真的么, 澳大利亚, 为什么你对WiFi 如此小气？：澳洲酒店顾客对Wi-Fi速度的满意度及其对公共Wi-Fi供给的启示 研究目的: 本研究分析了酒店的Wi-Fi 速度是否影响顾客满意度, 及其对致力于促进旅游业发展的商业和政府组织在提供Wi-Fi 服务上的启示 研究设计/方法/途径: 本研究结合191家澳洲酒店的数据以及111份对当地政府权威机关关于公共Wi-Fi供应的全国性调查的回复数据进行了回归分析, 并结合文献综述和对网上顾客评价进行了内容分析 研究发现: 如果Wi-Fi质量提高百分之一, 顾客满意度会相应提高0.376/100个单位。在酒店Wi-Fi质量普遍较好的地区, 由地方政府提供的公用Wi-Fi也会有更佳质量, 反之亦然。 实践意义: 不管是商业还是公共组织提供的Wi-Fi, 游客都重视它的持续性使用。对那些想要发展旅游的酒店和地方政府来说, 加大对Wi-Fi 质量的投入是必要的。然而, 为了推进此举, 国家政策应该根据此项研究的结果解决宽带基础设施的地域差异问题。 研究原创性/价值: 本研究 超越了传统意义上的公共和私有供给Wi-Fi的区别, 从业界和政府机关共同利益的角度出发来对这项关键的旅游基础设施进行研究。本文对英文文献关于Wi-Fi质量和顾客满意度的关系提供了支持, 并且为提高Wi-Fi质量的理论依据提供了创新性结论和讨论。